2007
DOI: 10.1016/j.ijsolstr.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A micro-mechanical investigation of bifurcation in granular materials

Abstract: In this paper, the notion of loss of sustainability of a mechanical state in a granular assembly is investigated. The vanishing of the second-order work, defined on the macroscopic scale from tensorial variables, is shown to play a fundamental role in detecting the occurrence of this type of bifurcation. Then a link is established between the macroscopic second-order work on the specimen scale and a discrete local expression that introduces microscopic variables defined on each contact scale. This relation ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 36 publications
3
75
0
Order By: Relevance
“…An everyday illustration of a bifurcation point is the vaporization temperature of water. Nevertheless, within our framework, Nicot and Darve [28] have shown that negative values of second-order work are related to a burst of kinetic energy, which is in agreement with the proposed definition. Under constant loading conditions, the mechanical state of the sample changes suddenly from a static regime to a dynamic one.…”
Section: Second-order Work Criterion Analysis Within a Phenomenologicsupporting
confidence: 88%
“…An everyday illustration of a bifurcation point is the vaporization temperature of water. Nevertheless, within our framework, Nicot and Darve [28] have shown that negative values of second-order work are related to a burst of kinetic energy, which is in agreement with the proposed definition. Under constant loading conditions, the mechanical state of the sample changes suddenly from a static regime to a dynamic one.…”
Section: Second-order Work Criterion Analysis Within a Phenomenologicsupporting
confidence: 88%
“…According to the evolutions of q and ε v against ε 1 under axial strain controlled drained compression, and as reported in Table 2, both numerical test specimens D 1 and D 2 confirm a typical behavior of a dense dry sand characterized by a dilatant change in volumetric behavior and a well marked peak. The peak in q indicates that a limit stress state is reached which also coincides with the vanishing of the second order work [18,30].…”
Section: Non-effective Versus Effective Localized Failurementioning
confidence: 78%
“…Both proportional paths led to the total liquefaction (more severe when stress-controlled) of the granular assembly marked by the vanishing of the principal stresses. As shown in [20,31], the passing of (σ 1 − σ 2 /R) through a peak with ε 1 indicates that a generalized limit state has been reached,at which the second order work [18,30] vanishes and pinpoints the occurrence of failure inside the Mohr-Coulomb limit.…”
Section: Non-effective Versus Effective Diffuse Failurementioning
confidence: 95%
“…Likewise, the consideration of microscopic aspects in the formulation of non-local constitutive theories for porous and granular materials are due to Nicot and Darve (2007); Yin et al (2009);Zhu et al (2010) and Xie et al (2011). Other remarkable works related to this matter were performed by Bonelli et al (2012); Jiang and Shao (2012); Shen et al (2012); Tran et al (2012); Shen et al (2013) and Shojaei et al (2014).…”
Section: Introductionmentioning
confidence: 99%